Editors' Note: Mediterranean Diet, Alzheimer Disease Biomarkers, and Brain Atrophy in Old Age. (11th January 2022) - Ganesh, Aravind; Galetta, Steven
Abstract : Dr. Ballarini et al. examined the relationship between following a Mediterranean-like diet and cognitive functions and in vivo biomarkers of Alzheimer disease (AD) in 512 patients in a cross-sectional analysis of the German DZNE-Longitudinal Cognitive Impairment and Dementia Study. Higher adherence to a Mediterranean-like diet was associated with larger medial-temporal grey matter volume, better memory, and less amyloid and phosphorylated-tau (p-tau) pathology in the CSF. Higher adherence favorably moderated associations among amyloid-beta 42/40 ratio, p-tau-181, and medial-temporal atrophy. In response, Dr. Brenner cites a previous study indicating that higher dietary spermidine content mediates the effects of adherence to a Mediterranean-like diet, with favorable volumetric and cortical measures in regions vulnerable to AD. Regarding potential underlying mechanisms for these associations, Dr. Brenner notes that age-related amyloid-beta and p-tau lead to dysfunctional autophagy and mitophagy, whereas bioactive compounds in Mediterranean-like diets may enhance autophagy and mitophagy, citing a spermidine supplementation trial that reported better cognitive function in patients with mild or moderate symptoms of cognitive decline. Responding to these comments, the authors agree that bioactive compounds such as spermidine in the Mediterranean-like diet are of interest in preventing neurodegeneration and dementia in addition to citing results from the LipiDiDiet trial, which showed slower cognitive and neuroradiologic decline in prodromal AD with early and prolonged multinutrient intervention. However, because most nutrient supplementation studies have shown insufficient evidence of efficacy, they suggest that dietary recommendations should focus on dietary patterns rather than specific nutrients. This exchange highlights our evolving understanding of the biological mechanisms by which brain-healthy diets such as the Mediterranean diet may exert cognitive benefits, while also demonstrating the challenges of disentangling the specific effects of different nutrients in these diets from the broad and complex effects of dietary patterns.